Complete PET Teacher`s Book - Heyderman Emma E. (Cambridge, Cambridge University Press, 2010)
Complete PET is a brand new course for the PET exam. It combines the very best in contemporary classroom practice with stimulating topics aimed at teenagers and young adults. The course covers every part of the PET exam in detail providing preparation, practice, information and advice to ensure that students are fully prepared for every part of the exam. Informed by Cambridge's unique searchable database of real exam scripts, the Cambridge Learner Corpus*, and providing an official PET past exam paper from Cambridge ESOL, Complete PET is the most authentic PET exam preparation course available.Complete PET Student's Book. contains 12 topic-based units. Each unit covers one part of each PET paper includes exercises targeting common PET candidate problem areas, using data from the Cambridge Learner Corpus includes an official past exam paper supplied by Cambridge ESOL the CD-ROM (for Windows XP and Vista) contains additional practice not in the Student's Book, including skills, grammar vocabulary and pronunciation the Writing and Speaking reference sections provide extra guidance for the Writing and Speaking papers contains a comprehensive Grammar reference section.Complete PET Teacher's Book: contains full teacher's notes with advice on classroom procedure and extra teaching ideas• the extra photocopiable material includes class activities, four progress tests, recording scripts and word lists.